Internet behavior patterns of adolescents before, during, and after COVID-19 pandemic - Wu, Qianying; Ren, Qihuan; Zhong, Na; Bao, Juwang; Zhao, Yan; Du, Jiang; Chen, Tianzhen; Zhao, Min (Frontiers in Psychiatry, 2022)
Background The outbreak of COVID-19 has affected the mental health of adolescents. To describe the Internet behavior transition patterns of adolescents and to understand the impact of clinical features on transition patterns during the COVID-19 pandemic. Method We conducted a cross-sectional cohort study using data collected through an online investigation in China. A total of 625 adolescents completed the online survey from May 15 to June 7, 2020. The adolescents were asked to retrospect to the Internet behaviors and game behaviors of three time periods: before the COVID-19 outbreak in China, during the COVID-19 outbreak in China, and back to school. The clinical variables of the demographic data, family functionality, and emotional and behavioral symptoms were also collected. Results Four Internet behavior transition pattern during the COVID-19 was identified: (1) Continuous normal group (55.52%); (2) Normal to Internet Addiction Group (5.28%); (3) Internet Addiction to Normal Group (14.56%); (4) Continuous Internet Addiction Group (24.64%). Years of education, academic score ranking, family functionality, and emotional and behavioral symptoms were different across the four groups. Proportions of game behaviors, scores of Strengths and Difficulties Questionnaire (SDQ) and SDQ subscale at the period before the COVID-19 outbreak were significant in predicting transition patterns. Conclusions The Internet behavior patterns of adolescents in the COVID-19 period were various. Clinical features before the COVID-19 pandemic may predict transition patterns. The heterogeneity in characteristics between different transition patterns should be considered when intervening in adolescents' problematic Internet behavior.